PENGARUH MEDIA KUNANG-KUNANG HITUNG (FIREFLY MATH) TERHADAP KEMAMPUAN BERHITUNG PESERTA DIDIK KELAS 2 SEKOLAH DASAR - Siti Nurhalizah; Muhammad Sofwan; Violita Zahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to find out the effect of the use of Firefly Math Media on the arithmetic skill of second-grade students at SD Negeri 55/I Sridadi. The research design used a quantitative approach involving two classes, namely class 2D as the experimental class (13 students) and class 2C as the control class (17 students). Data were collected through pre-test and post-test, then analyzed using the SPSS 29 program. The results of the descriptive analysis showed that the average pre-test scores of both groups were relatively comparable (42,85 and 44,13). After treatment, the average score of the experimental class increased to 58,31, while the control class was 53,00, with a difference of 5,31 points. The normality and homogeneity assumption tests showed that the data were normally distributed and homogeneous. Analysis using Mixed Design ANOVA showed that the time factor had a significant effect on students' scores. Thus, it can be concluded that the use of Firefly Math Media is effective in improving students' arithmetic ability.